Varied response of underground and aboveground plant matter: functional diversity of three different vegetational types after translocation to reclaimed postindustrial land. (27th August 2019) - Świerszcz, Sebastian; Nobis, Marcin; Maślak, Magdalena; Smieja, Agata; Kojs, Paweł; Nowak, Sylwia; Nowak, Arkadiusz
Abstract: The indicators of functional diversity are increasingly used to assess the conservation effectiveness of the most valuable habitats. However, little is known about the response of functional traits, their diversity, and divergence in plant communities after translocation. To assess how functional diversity changes on dry heath, meadow, and fen after translocation of entire turfs of vegetation from an airport area to the Botanical Garden in Radzionków, we used leaf–height–seed (LHS) traits (specific leaf area, height, and seed mass) and vegetative traits (bud bank size, bud bank depth, and lateral spread). We also measured community weighted means and multifunctional diversity metrics (functional richness, evenness, and divergence) for all the traits and for LHS and vegetative traits separately. On the basis of our results, we found that the most sensitive type of vegetation to changes in functional diversity is meadow, where an increase in functional evenness and divergence were observed. The functional richness increased also for the LHS traits set in meadow plots. The response to the translocation on dry heath was a decline in functional richness and an upswell of functional evenness and divergence of vegetative reproduction traits. Additionally, we observed changes in community weighted means on meadow and dry heath. Fen was the most resistant to alterations in functional diversity after translocation. Despite the changes in functional diversity and community weighted means being significant, the shift in values of particular indices was not considerable. Our results may provide a better insight into function changes in translocated vegetation plots.